Movement and stretching imagery during flexibility training - Vergeer, I.; Roberts, J. (Journal of Sports Sciences, 2006)
The aim of this study was to examine the effect of movement and stretching imagery on increases in flexibility. Thirty volunteers took part in a 4 week flexibility training programme. They were randomly assigned to one of three groups: (1) movement imagery, where participants imagined moving the limb they were stretching; (2) stretching imagery, where participants imagined the physiological processes involved in stretching the muscle; and (3) control, where participants did not engage in mental imagery. Active and passive range of motion around the hip was assessed before and after the programme. Participants provided specific ratings of vividness and comfort throughout the programme. Results showed significant increases in flexibility over time, but no differences between the three groups. A significant relationship was found, however, between improved flexibility and vividness ratings in the movement imagery group. Furthermore, both imagery groups scored significantly higher than the control group on levels of comfort, with the movement imagery group also scoring significantly higher than the stretching imagery group. We conclude that the imagery had stronger psychological than physiological effects, but that there is potential for enhancing physiological effects by maximizing imagery vividness, particularly for movement imagery.